PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA MIO J (STUDI KASUS PADA PT YAMAHA BAHANA TEGAL) - Dimas Pratama; Apriatni EP (Jurnal Ilmu Administrasi Bisnis, 2016)
Brand image and product quality is an element that can influence purchasing decisions. PT.Yamaha Bahana Tegal is a company engaged in the marketing of Yamaha brand motorcycles. Ifconsumers have a good impression or positively impact brand image and product quality of aproduct then it will affect a high purchasing decisions by consumers. Strengthening brand imageand good product quality is also used companies motorcycle to win the competition.This type of research uses explanatory research, with a population of 85 respondents whouse and buy Yamaha Mio motorcycle in 2014 PT. Yamaha Bahana Tegal by way of random.Data were collected through a questionnaire with Likert scale measurement. Methods of dataanalysis used correlation, simple regression, multiple regression using SPSS.This study concluded that the brand image and product quality influence on purchasingdecisions, either partially or stimultan. The variable quality of the products have a greaterinfluence than the variable brand image.Suggestions can be submitted to PT.Yamaha Bahana Tegal is preferably often remindingconsumers to serve when it entered the time, adding features in the latest such answer backsystem to facilitate the user when it is a public parking lot, adding cubical centimeters on enginecapacity in order machines do not heat quickly and the durability of the machine awake